Evaluasi Sistem Informasi Akademik E-Campus Universitas Pelita Bangsa Dengan Metode Pieces - Arif Susilo; Muhtajuddin Danny (Teknik Informatika, Universitas Pelita Bangsa, 2023)
The purpose of an Academic Information System evaluation is to find out the quality of the Academic Information System being evaluated. The output value of this evaluation is a subjective assessment including Very Good, Good, Moderate, Bad, Very Bad. The Pelita Bangsa University eCampus Academic Information System has been used for several years, but the system has never been evaluated whether it can still meet user needs. In the future, this will make it difficult to develop systems to support campus operations in the medium and long term. For this reason, researchers are trying to conduct research to determine system performance with the PIECES method. Analysis was carried out to identify the strengths and weaknesses of the system that has been used by Pelita Bangsa University, with the PIECES Framework analysis method, which consists of analysis points, namely: Performance, Informations and data, Economics, Control and security, Efficiency, and Service where the points This becomes a reference for evaluation and analysis of an information system. The results of this study are expected to be able to find out some of the advantages or strengths of the system that can support the development and progress of education at Pelita Bangsa University. The results of this study are also expected to show the shortcomings and weaknesses of the system, so that the existing system needs improvement or refinement towards a better direction. Besides that, it can also be shown the results of research on the level of student satisfaction with academic administration services. Keywords: System Evaluation, e-Campus, PIECES Method